Three-phase dry-type distribution transformers 50 Hz, from 100 to 2500 kVA with highest voltage for equipment not exceeding 36 kV. Supplementary requirements for transformers with highest voltage for equipment equal to 36 kV Part 2, (15th August 1996) - British Standards Institution,
No abstract available